THEORY OF EVOLUTION OF ALL LIFE ON EARTH - Rao, Y. V. Subba; Rao, Y. V. Ramana (International Journal of Research -GRANTHAALAYAH, 2022)
‘Origin of Life’ is critical to Evolution of heritable change of organisms over multiple generations. The process of encoding information in DNA in the ‘Panspermia Origin of Life’ and decoding the same in ‘Evolution’ ought not to be different for the proposed process to be true. In the present study, it is observed that the process of decoding information in DNA in ‘Evolution’ is just the reverse process of encoding DNA in ‘Panspermia Origin of Life’ that works on the principle of electromagnetism with its usual frequencies, oscillations, energies and resonances. Incidentally, the present hypothesis provides a more viable and reasonable theory of evolution of heritable organisms over multiple generations, in contradistinction to Darwin’s Theory of Evolution and Natural Selection.